Shifting Developmental Trajectories During Critical Periods of Brain Formation - Dehorter, Nathalie; Del Pino, Isabel (Frontiers in Cellular Neuroscience, 2020)
Research on critical periods of brain development is greatly expanding our understanding of the cellular and molecular mechanisms underlying the epochs of heightened plasticity driven by environmental influence. Novel studies have started to reveal that timely interventions during critical periods hold potential to reorient abnormal developmental trajectories in animal models of neurological and neuropsychiatric disorders. In this review, we re-examine the fundamental criteria that characterize a critical period, highlighting the recently discovered mechanisms of developmental plasticity in health and disease. In addition, we touch upon technological improvements in modelling critical periods in human-derived neural networks in vitro. These scientific advances associated with the use of developmental manipulations of the immature brain represent a promising and new preclinical setting that will allow the future translatability of timely interventions into clinical applications for neurodevelopmental disorders such as intellectual disability, autism spectrum disorders and schizophrenia.